Normative Review of Legal Authority and Certainty in Land Tax Determination Based on NJOP in Indonesia - Abdullah Jamaludin; Hari Purwadi; Isharyanto Isharyanto (CV. Dyoqu Publishing and Management, 2025)
Background:Disparities in land taxation frequently emerge in Indonesia, triggered by differing valuation practices between local fiscal authorities and national tax offices. The application of NJOP as the tax base often clashes with actual sale values, generating uncertainty in legal interpretation. Aims:This paper investigates the extent of legal authority held by local governments in imposing taxes on land transactions using NJOP as a benchmark. It also explores the implications for legal clarity and the rights of taxpayers amid conflicting institutional assessments. Method:Utilizing a normative legal framework, this study engages in statutory and conceptual analysis. Data were obtained from statutory regulations and scholarly sources to examine the alignment of valuation practices with principles of fairness, legal authority, and taxpayers’ protection under Indonesian tax law. Result:The analysis uncovers overlapping mandates between regional and central agencies, leading to ambiguity in land value assessment. While NJOP is recognized in law, its rigid application without reference to actual transaction prices can erode the fairness of taxation and compromise legal assurance. The lack of unified regulatory standards exacerbates confusion for both taxpayers and institutions. Conclusion:A coherent legal structure is essential to synchronize valuation principles in land taxation. Establishing clearer institutional boundaries and reaffirming legal certainty are vital steps to ensure equitable tax enforcement in property transactions. dministrasi negara.